Strategies that promote student engagement : unleashing the desire to learn - Riggs, Ernestine Gates, 1938-; Gholar, Cheryl Renee; Gholar, Cheryl Renee. Connecting with students' will to succeed (Thousand Oaks, Calif. : Corwin Press, 2009)
From the Publisher: Featuring updated research, grade- specific individual and group activities, and suggestions for assessment, this resource outlines how teachers can inspire their students to become self-motivated learners.
Revised ed. of: Connecting with students' will to succeed : the power of conation / Cheryl Gholar & Ernestine Riggs.
Includes bibliographical references and index.
Keywords: Motivation in education; Teacher-student relationships